Animal Models of Temporomandibular Joint Osteoarthritis: Classification and Selection - Zhao, Yuqing; An, Yanxin; Zhou, Libo; Wu, Fan; Wu, Gaoyi; Wang, Jing; Chen, Lei (Frontiers in Physiology, 2022)
Temporomandibular joint osteoarthritis (TMJOA) is a common degenerative joint disease that can cause severe pain and dysfunction. It has a serious impact on the quality of lives of patients. Since mechanism underlying the pathogenesis of TMJOA is not fully understood, the development of effective tools for early diagnosis and disease-modifying therapies has been hindered. Animal models play a key role in understanding the pathological process of diseases and evaluating new therapeutic interventions. Although some similarities in disease processes between animals and humans are known, no one animal model is sufficient for studying all characteristics of TMJOA, as each model has different translatability to human clinical conditions. For the past four decades, TMJOA animal models have been studied by numerous researchers and can be broadly divided into induced or spontaneous models. The induced models can be divided into invasive models (intra-articular injection and surgical induction) or non-invasive models (mechanical loading, high-fat diet, and sleep deprivation). The spontaneous models include naturally occurring and genetically modified models. Different types of animal models simulate different pathological expressions of TMJOA and have their unique characteristics. Currently, mice, rats, and rabbits are commonly used in the study of TMJOA. This review sought to provide a general description of current experimental models of TMJOA and assist researchers in selecting the most appropriate models for different kinds of research.